Harbor Porpoise (Phocoena phocoena) Reaction to a 3D Seismic Airgun Survey in the North Sea - Sarnocińska, Joanna; Teilmann, Jonas; Balle, Jeppe Dalgaard; van Beest, Floris M.; Delefosse, Matthieu; Tougaard, Jakob (Frontiers in Marine Science, 2020)
The most common cetacean in the North Sea is the harbour porpoise (Phocoena phocoena). Underwater noise is increasingly recognised as a source of impact on the marine environment, and 3D seismic and airguns were are one some of the first man-made high intensity sound sources to receive attention with respect to potential impact on marine mammals. In this study, we investigate the effects of a 3D seismic survey on harbour porpoise echolocation activity in the Danish sector of the North Sea. This was achieved by deploying porpoise click detectors (C-PODs) and sound recorders (SM2M and SM3M) both inside and adjacent to the seismic survey area, before, during and after the survey over a (total study time wasduration of nine months in total). Three echolocation parameters were analysed: number of clicks per minute, minutes with porpoise echolocation click trains and feeding buzz frequency in relation to all minutes with click trains. Decreases in echolocation signals were detected up to 8-12 km from the active airguns, which may indicate temporary displacement of porpoises or a change in porpoise echolocation behaviour. No general displacement of harbour porpoises away from the seismic survey area could be detected when comparing to reference stations 15 km away from any seismic activity. However, nNo general displacement of harbour porpoises away from the seismic survey area could be detected when comparing to reference stations 15 km away from any seismic activity. decreases in recorded echolocation signals were detected up to 8-12 km from the active airguns, which indicate temporary displacement of porpoises and/or a change in porpoise echolocation behaviour. Our results add to the understanding that underwater noise has the potential to affect temporarily foraging efficiency in porpoises. While the effect of seismic surveys on harbour porpoise behaviour was smaller than what has been found for pile-driving, the cumulative effect of the different anthropogenic impacts should could be performed assessed by evaluation of potential population level consequences.